Why Three? An exploration of the origins of the doctrine of the Trinity with reference to Platonism and Gnosticism - Gaston, T (2014)
In this thesis I explore the emergence of the Christian triad with reference to two contemporary movements: Middle Platonism and Gnosticism. The earliest Christian writer to enumerate the three constituents of what would become the Christian Trinity is Justin. In addition to his three extant works, Justin’s triadology can be diagnosed from those he directly influenced – Tatian and Athenagoras – who I have (somewhat artificially) grouped under the heading the “school of Justin”. The ontological triad adopted by these Christian thinkers is compared with the triads of Middle Platonism and Gnosticism, both in terms of their structure and in terms of the function and ontological status of the individual constituents of these triads. In this thesis I propose that a liturgical triad of primitive Christianity, the trine baptismal formula, was conflated by the “school of Justin” with the ontological triad of Middle Platonism, resulting in three referents of the baptismal formula being embued with new functions and ontological status. Whilst emerging as a hierarchical triad, the logic of Platonic ontology when combined with Christian tradition required the sharp distinction between God, as Being, and all other things resulting in a Christian triad that was also a unity. This new triad became fixed as a central tenet of Christianity. I find no plausible connection between any known Gnostic triad and the triad of the “school of Justin”. There is some interaction between Gnostic and Platonic thought during this period. It is possible that the Triple-Powered One pre-empted the Being-Mind-Life triad of Neoplatonism.